Beclin-1–Dependent Autophagy Improves Outcomes of Pneumonia-Induced Sepsis - Nikouee, Azadeh; Kim, Matthew; Ding, Xiangzhong; Sun, Yuxiao; Zang, Qun S. (Frontiers in Cellular and Infection Microbiology, 2021)
Objective We previously demonstrated that promoting Beclin-1–dependent autophagy is cardiac protective during endotoxemia shock, suggesting that autophagy-based approaches may become a promising therapeutic strategy for sepsis. In this study, we applied both genetic and pharmacological approaches to evaluate whether Beclin-1 activation improves sepsis outcomes in a model of pneumonia-induced sepsis. Methods Sepsis was induced in mice by Klebsiella pneumoniae infection via intubation, and outcomes of clinical sickness scores, systemic infection, inflammation, survival, and pulmonary pathology were examined. Evaluation of Beclin-1 activation was achieved by comparing strains of C57BL/6J wild type and Becn1F121A that carries a transgenic expression of Beclin-1–active mutant F121A, and by comparing animal groups treated with Beclin-1–activating peptide, Tat-beclin-1 peptide (TB-peptide), or with vehicle control. The status of autophagy in the lung tissue was examined in autophagy reporter mice, CAG-RFP-EGFP-LC3, by fluorescence microscopy. Results Pulmonary infection by K. pneumoniae produced an insufficient, maladaptive autophagy in the lung. Activation of Beclin-1 by forced expression of active mutant Becn1F121A or by treatment with TB-peptide enhanced autophagy and significantly reduced sickness scores, systemic infection, and circulating and pulmonary cytokine production. Both approaches demonstrated notable benefits in limiting post-infection pathogenesis in the lung, such as decreases in alveolar congestion, hemorrhage, infiltration of inflammatory cells, and alveolar wall thickness. Conclusion Data suggest that targeted activation of Beclin-1 alleviates adverse outcomes of pneumonia-induced sepsis, and thus, possess a therapeutic potential.